2004
DOI: 10.1097/01.shk.0000129338.99410.5d
|View full text |Cite
|
Sign up to set email alerts
|

A Prostaglandin E2 Receptor Subtype Ep4 Agonist Attenuates Cardiovascular Depression in Endotoxin Shock by Inhibiting Inflammatory Cytokines and Nitric Oxide Production

Abstract: The prostaglandin (PG) E2 receptor subtype EP4 has been found to mediate regulation of inflammatory cytokines in macrophages and neutrophils in vitro by PGE2. Yet the role of EP4 receptors in endotoxin shock in vivo and whether EP4 activation is a beneficial treatment are not clear. We tested the effect of an EP4 agonist on hemodynamic changes and production of inflammatory cytokines in a rat endotoxin-induced shock model. In rats under pentobarbital anesthesia, lipopolysaccharide (LPS) was injected, and an EP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 31 publications
(34 reference statements)
3
20
0
Order By: Relevance
“…This is consistent with the previous finding that PGE 2 and EP4 agonists attenuated LPS-induced cytokine production in mice (40). However, a number of studies have provided evidence that COX inhibitors can improve survival after the onset of endotoxic shock and COXdeficient mice are resistant to endotoxin-induced inflammation and death (17,19,41).…”
Section: Figuresupporting
confidence: 82%
“…This is consistent with the previous finding that PGE 2 and EP4 agonists attenuated LPS-induced cytokine production in mice (40). However, a number of studies have provided evidence that COX inhibitors can improve survival after the onset of endotoxic shock and COXdeficient mice are resistant to endotoxin-induced inflammation and death (17,19,41).…”
Section: Figuresupporting
confidence: 82%
“…EP4-selective agonists therefore represent a novel class of immune-modulator drugs that could be useful for the management of inflammatory diseases such as arthritis (Shibata-Nozaki et al, 2011), sepsis (Sakamoto et al, 2004), inflammatory pain (Omote et al, 2002), and colitis (Kabashima et al, 2002;Nitta et al, 2002;Jiang et al, 2007Jiang et al, , 2010. In a human study, patients with UC refractory to 5-ASA responded favorably to treatment with [[3-[[(1R) (Nakase et al, 2010).…”
Section: Ep4 Agonist-plga Ms Prevents Colitis In Mice 345mentioning
confidence: 99%
“…We have previously found that 15dPGJ 2 is a negative regulator of NO levels in the embryo from control and mild diabetic rats during embryo organogenesis . NO concentrations have also been found to be regulated by PGE 2 in different tissues (Paliege et al 2004, Sakamoto et al 2004. On the other hand, NO is a positive regulator of PGE 2 concentrations during embryo organogenesis in both control and mild diabetic rats (Jawerbaum et al 1998).…”
Section: Introductionmentioning
confidence: 99%